Fostering product innovation by learning through exporting in Eastern Europe - Bulgakova, Iuliia (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
This study discusses the importance of learning through the process of exporting, and more specifically how such a process can enhance the product innovativeness of a company. The purpose of this study is to investigate the appropriate sources of learning and to suggest an interactive framework for how new knowledge from exporting markets can materialize itself into product innovation. The theoretical background of the study was constructed from academic literature, which is related to concepts of learning by exporting, along with sources for learning in the market and new product development. The empirical research in the form of a qualitative case study was based on four semi-structured interviews and secondary data from the case company official site. The interview data was collected between March and April 2015 from case company employees who directly work in the department of exporting and product development. The method of thematic analysis was used to categorize and interpret the collected data. What was conclusively discovered, was that the knowledge from an exporting market can be an incentive for product innovation, especially an incremental one. Foreign customers and competitors as important sources for new knowledge contribute to the innovative process. Foreign market competitors’ influence on product improvements was high only when the competitor was a market leader or held a colossal market share, while the customers’ influence is always high. Therefore, involving a foreign customer in the development of a new product is vital to a company that is interested in benefiting from what is learned through exporting. The interactive framework, which is based on the theoretical background and findings of the study, suggests that exporting companies can raise their product innovativeness by utilizing newly gained knowledge from exporting markets. Except for input, in the form of sources of learning, and product innovation as an output, the framework contains a process of knowledge transfer, the absorptive capacity of a firm and a new product development process. In addition, the framework and the findings enhance the understanding of the disputed relationship between an exporting experience and product innovation. However, future research is needed in order to fully understand all the elements of the framework, such as the absorptive capacity of a firm as well as more case companies to be processed in order to increase the generalization of the framework